Modelamiento y simulación del sistema de información agrario en el cultivo de arroz para el apoyo en la toma de decisiones en la región San Martín - Grández Pezo, Alberto (2006)
Half way structured problems are those that have elements or relations than sometime they are out of control. But always they prove to be difficult in a time of presenting solution alternatives without the benefit of a methodology in order to such end designed. At the present time there are methodologies that they allow us to discuss these problems and to define its structure to what later we can understand its behaviour. That’s why this argument that we make use in this study to discuss the problem that at present rice sower show us in the region and the country, where we made use of a methodology that is not new in his appearing, but even well, in his application in our midway, I mean specifically to the Dynamic of System, as a methodology to study complex systems, and proposing solutions alternatives The activity ric e sower in her Region San Martin and the country always has been identified as a problem from the point of view of the offer and the request, becoming converted in a fact very delicate situation, enclosure it has been used in political situations, where what making use of System Vision we have detected that the core of the problem is mainly in planning the rice sower activity. And identifying to the DIA-SM as an responsible entity of the said-activity pacification, and besides, making use of the methodology of dynamic system we have constructed a simulation model called MODA to the DIA-SM to the help in realization of his work. MODA as a technique of projection will help in the process of elaboration of the cultivation of the rice in the country, that will permit us obtain an ordered and systematized production of the activity rice sower, and in this way we would contribute with the farmers in getting better economic incomes, Decreasing considerably uncertainty than at present the farmer has to face in each campaign